Case reportsSoft tissue infection caused by Streptococcus dysgalactiae subsp. equisimilis possessing group Aantigen: a case report and review of the literature - Karyński, Michał; Łętowska, Iwona; Grzesiowski, Paweł (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
The study presents microbiological characteristics, identification, pathogenicity, epidemiology and antimicrobial susceptibility of Streptococcus dysgalactiae subsp. equisimilis (SDSE). The SDSE shows a close relationship to Streptococcus pyogenes. The SDSE strains usually have a group G antigen, less commonly a group C one. Like S. pyogenes , most of SDSE strains can cause complete hemolysis (β-hemolysis) on a blood agar medium, and some of them possess the same A type of group-specific cell wall antigen. These common phenotype traits lead to confusion between both species. For this reason, microbiological diagnosis of streptococci should not be finished at the stage of serogrouping. A case of soft tissue infection of the left lower limb of a 30-year-old man is described. The etiological factor of the infection was β-hemolytic SDSE of group A. Antimicrobial susceptibility tests revealed that the strain is susceptible to penicillin, erythromycin, clindamycin and levofloxacin, while it is resistant to tetracycline. Treatment with first-generation cephalosporin (cefadroxil) was successfully applied, resulting in a complete remission of the infection symptoms.